2014
DOI: 10.2109/jcersj2.122.430
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and structural effects on ionic conductivity at columnar grain boundaries in yttria-stabilized zirconia thin films

Abstract: This study elucidated the effects of coherence and chemical composition on ionic conductivity at columnar grain boundaries of 6 mol % Y 2 O 3 doped ZrO 2 (YSZ) thin films. The YSZ thin films were deposited with several orientation textures on MgO (100), Al 2 O 3 (102), and SiO 2 -glass substrates using metalorganic chemical vapor deposition (MOCVD). Impedance measurements revealed the total ionic conductivity of the thin films. The activation energy of the ionic conduction of YSZ thin films on MgO or Al 2 O 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Data from several studies [12,13] suggest that columnar grain boundaries act as barriers for oxygen diffusion, and columnar grain boundaries act as rapid diffusion paths. Contrary to the previously published studies, T. Kiguchi et al demonstrated that total ionic conductivity was restricted by the columnar growth, and columnar structure with high coherence was preferred [14,15].…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…Data from several studies [12,13] suggest that columnar grain boundaries act as barriers for oxygen diffusion, and columnar grain boundaries act as rapid diffusion paths. Contrary to the previously published studies, T. Kiguchi et al demonstrated that total ionic conductivity was restricted by the columnar growth, and columnar structure with high coherence was preferred [14,15].…”
Section: Introductionmentioning
confidence: 67%
“…The influence of deposition rate and substrate temperature on the phase structure of the Cu-Mo films was examined using the approaches based on the phase-field models by Derby et al [35] and Ankit et al [36]. By using the kinetic Monte Carlo approaches, the effects of substrate tilt angle [37], substrate temperature [38], deposition rate [13,14], and composition [39] on the phase structure of nanocomposites have been recently investigated. Bouaouina et al in [37] discovered that the surface roughness and the phase structure of TiN thin films are influenced by the change of substrate tilt angle: an increase in the substrate tilt angle caused an increase in the tilt angle of TiN columns and the surface roughness as well.…”
Section: Introductionmentioning
confidence: 99%